The usage of OBike among students - Abdul Kadir, Hasnah; Wan Ahmad, Wan Khairi; Noorfuad, Noorhannah; Nazari, Nur Syahirah; Wok, Saodah (2018)
The emergence of communication technology with the combination of contemporary public transportation creates OBike, a new generation of public bicycle where users can move faster and cheaper while contributing towards a greener environment. They can ride, park and pay anytime at any place by using their smartphone application. This study aims to gauge the usage of OBike among students at the International Islamic University Malaysia (IIUM), Gombak campus. In using the innovation attributes (relative advantage, simplicity, compatibility, trialability, and observability) of the Diffusion of Innovation Theory, this study measures the adoption level of users of the new technology - OBike. Thus, the objectives of this study are to analyse the relationship between the usage of OBike and the innovation attributes, besides to test the best predictor of using the OBike. A quantitative research design using the survey method with a self-administered questionnaire is used as a tool for data collection. A total of 230 students responded to this survey. The results show that all innovation attributes have a positive relationship with the usage of OBike. The relative advantage of the innovation attributes is the best predictor. Hence, this study concludes that students believe that there are many advantages in using the OBike. However, it is not easy for them to use it as there is a negative relationship between simplicity and usage.